101 Risk Factors and Outcomes of Postoperative Complications in Adult Patients With Moyamoya Disease. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Zhao, Meng; Zhao, Jizong
Abstract: INTRODUCTION: The risk factors and clinical significance of postoperative complications in moyamoya disease are still unclear. The aim of this study is to investigate the predictors of postoperative complications in moyamoya disease and examine the impact of complications on outcomes. METHODS: We reviewed consecutive adult moyamoya disease patients who underwent either indirect, direct, or combined bypass surgery in our hospital between 2009 and 2015. Preoperative clinical characteristics and radiographic features were recorded. Postoperative complications within 14 d after surgery were examined. We conducted multivariate logistic regression analyses to identify the risk factors for either postoperative ischemia or postoperative cerebral hyperperfusion. Outcomes including recurrent strokes and neurological status (modified Rankin scale, mRS) during follow-up were collected. We compared outcomes in patients who had complications with those without complications, using propensity score analysis to account for between-group differences in baseline characteristics. RESULTS: A total of 500 patients (610 hemispheres) were included in this study. Postoperative complications were observed in 74 (12.1%) operations, including 30 (4.9%) new postoperative ischemia, 27 (4.4%) hyperperfusion, 12 (2.0%) impaired wound healing, and 6 (1.0%) subdural effusion. We identified advanced Suzuki stage (odds ratio [OR] 1.669, 95% confidence interval [CI] 1.059-2.632, P = .027) and preoperative ischemic presentation (OR 5.845, 95% CI 1.654-20.653, P = .006) to be significantly associated with postoperative ischemia. Preoperative ischemic presentation (OR 5.73, 95% CI 1.27-25.88, P = .023) and admission mRS (OR 1.81, 95% CI 1.06-3.10, P = .031) were significantly associated with postoperative symptomatic hyperperfusion syndrome. Compared to patients without postoperative complication, patients who experienced any postoperative complications had longer hospital stay and worse mRS at discharge (both P < .0001). At the final follow-up, no significant difference in functional disability (mRS 3-6, 11.9% vs 4.5%, P = .116) and future stroke events ( P = .513) between the 2 groups were detected. CONCLUSION: Advanced Suzuki stage and preoperative ischemic presentation were independent risk factors for postoperative ischemia; the mRS on admission and preoperative ischemic presentation were independently associated with postoperative cerebral hyperperfusion syndrome. Although patients with postoperative complications had worse neurological status at discharge, postoperative complications had no associations with future stroke events or functional disability during follow-up.